Power relations in the twenty-first century mapping a multipolar world? - Murray, Donette; Brown, David (Contemporary security studies, 2018)
This volume critiques contemporary power trends by examining key bilateral dynamics between five putative 'poles' of the multipolar order in the twenty-first century. The volume aims to deepen understanding of power trends and critically assess the individual inter-dynamics at play. It concludes by returning the focus to the central questions of if, how and when a post-American, multipolar world could develop. This volume will be of much interest to students of global security, foreign policy, and IR in general.